Method for manufacturing electrophotographic photoreceptor
Patent Information
- Application Number
- JP2023117092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
【0006】 <1>、<3>、<4>又は<5>によれば、電荷輸送層を形成する直前の電荷発生層に含まれる溶剤量が0.1ppm未満又は500ppm超である場合、または、電荷輸送層を形成する直前の電荷発生層に含まれる溶剤のHSPと電荷輸送層を形成する塗布液に含まれる結着樹脂のHSPとの距離Raが8未満又は10超である場合に比べて、感光層の層厚均一性に優れる電子写真感光体を生産性よく製造する製造方法が提供される。 <2>によれば、電荷輸送層を形成する塗布液がポリアリレート樹脂を含まない場合に比べて、電子写真感光体の感光層が耐摩耗性に優れる。 <6>によれば、感光層の層厚均一性に優れる電子写真感光体が製造される。
Smart Images

Figure 2025014495000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing an electrophotographic photoreceptor. [Background technology]
[0002] Patent Document 1 discloses a method for producing an electrophotographic photoreceptor, in which, when forming an electrophotographic photoreceptor on a conductive support using a coating liquid for a charge generation layer and then a coating liquid for a charge transport layer, the coating liquid for the charge generation layer is coated and then dried at room temperature, and after coating the coating liquid for the charge transport layer, i) a heat treatment is performed at a temperature equal to or higher than the boiling point (A) of the solvent used and equal to or lower than the glass transition point (B) of the charge transport layer, and ii) a re-heat treatment is performed at a temperature equal to or higher than the glass transition point (B) and 50°C to 70°C higher than the boiling point (A). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-242784 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present disclosure has an object to provide a manufacturing method for efficiently manufacturing an electrophotographic photoreceptor having a photosensitive layer with excellent layer thickness uniformity, compared to a case in which the amount of solvent contained in the charge generating layer immediately before the formation of the charge transport layer is less than 0.1 ppm or more than 500 ppm, or a case in which the distance Ra between the HSP of the solvent contained in the charge generating layer immediately before the formation of the charge transport layer and the HSP of the binder resin contained in the coating liquid that forms the charge transport layer is less than 8 or more than 10. [Means for solving the problem]
[0005] Specific means for solving the above problems include the following aspects. <1> A method for producing an electrophotographic photoreceptor comprising: a conductive substrate; and a photosensitive layer having a charge generating layer and a charge transport layer disposed on the conductive substrate, the method comprising the steps of: forming the charge generating layer on the conductive substrate by coating; forming the charge transport layer on the surface of the charge generating layer by dip coating; the amount of solvent contained in the charge generating layer immediately before forming the charge transport layer is 0.1 ppm or more and 500 ppm or less; a distance Ra between an HSP of a solvent contained in the charge generating layer immediately before forming the charge transport layer and an HSP of a binder resin contained in a coating liquid for forming the charge transport layer is 8 or more and 10 or less; A method for manufacturing an electrophotographic photoreceptor. <2> The binder resin contains a polyarylate resin. <1> 13. A method for producing an electrophotographic photoreceptor according to claim 12. <3> The thickness of the charge transport layer is 30 μm or more and 50 μm or less. <1> or <2> 13. A method for producing an electrophotographic photoreceptor according to claim 12. <4> the viscosity of the coating liquid for forming the charge transport layer is 500 mPa·S or more and 1000 mPa·S or less; <1> ~ <3> 13. A method for producing an electrophotographic photoreceptor according to claim 12, <5> In the dip coating for forming the charge transport layer, the pull-up speed is 100 mm / min or more and 200 mm / min or less. <1> ~ <4> 13. A method for producing an electrophotographic photoreceptor according to claim 12, <6> <1> ~ <5> 13. An electrophotographic photoreceptor manufactured by the method for manufacturing an electrophotographic photoreceptor according to claim 12. Effect of the Invention
[0006] <1> , <3> , <4> or <5> This provides a manufacturing method for efficiently manufacturing an electrophotographic photoreceptor having excellent uniformity in the thickness of a photosensitive layer, compared to when the amount of solvent contained in the charge generating layer immediately before the formation of the charge transport layer is less than 0.1 ppm or more than 500 ppm, or when the distance Ra between the HSP of the solvent contained in the charge generating layer immediately before the formation of the charge transport layer and the HSP of the binder resin contained in the coating liquid that forms the charge transport layer is less than 8 or more than 10. <2> According to the present invention, the photosensitive layer of the electrophotographic photoreceptor has excellent abrasion resistance as compared with the case where the coating liquid for forming the charge transport layer does not contain a polyarylate resin. <6> According to this, an electrophotographic photoreceptor having a photosensitive layer with excellent thickness uniformity can be manufactured. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a partial cross-sectional view showing an example of a layer structure of an electrophotographic photoreceptor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.
[0009] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.
[0010] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved.
[0011] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.
[0012] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.
[0013] In the present disclosure, unless otherwise specified, the alkyl group and the alkylene group include any of straight-chain, branched, and cyclic groups.
[0014] In the present disclosure, a hydrogen atom in an organic group, an aromatic ring, a linking group, an alkyl group, an alkylene group, an aryl group, an aralkyl group, an alkoxy group, an aryloxy group, and the like may be substituted with a halogen atom.
[0015] In the present disclosure, when a compound is shown by a structural formula, the symbols (C and H) representing carbon atoms and hydrogen atoms in the hydrocarbon group and / or hydrocarbon chain may be omitted.
[0016] In the present disclosure, the term "structural unit" of a copolymer or resin is synonymous with a monomer unit.
[0017] In the present disclosure, the "axial direction" of an electrophotographic photosensitive member means the direction in which the rotation axis of the electrophotographic photosensitive member extends, and the "circumferential direction" of an electrophotographic photosensitive member means the rotation direction of the electrophotographic photosensitive member.
[0018] In this disclosure, ppm is an abbreviation for parts per million and is based on mass.
[0019] <Method of Manufacturing Electrophotographic Photoreceptor> The manufacturing method according to the present embodiment is a method for manufacturing an electrophotographic photoreceptor including a conductive substrate and a photosensitive layer having a charge generating layer and a charge transport layer disposed on the conductive substrate. Hereinafter, the "electrophotographic photoreceptor" is also referred to as a "photoreceptor".
[0020] Fig. 1 is a partial cross-sectional view showing an example of the layer structure of a photoreceptor. The photoreceptor 10A shown in Fig. 1 has a structure in which an undercoat layer 2, a charge generation layer 3, and a charge transport layer 4 are laminated in this order on a conductive substrate 1, and the charge generation layer 3 and the charge transport layer 4 constitute a photosensitive layer 5 (a so-called function-separated photosensitive layer). The photoreceptor 10A may have an intermediate layer (not shown) between the undercoat layer 2 and the charge generation layer 3. The photoreceptor 10A may have a protective layer (not shown) on the charge transport layer 4. The undercoat layer 2 may or may not be present.
[0021] The manufacturing method according to this embodiment includes the steps of: forming a charge generating layer on a conductive substrate by coating; forming a charge transport layer on the surface of the charge generating layer by dip coating; the amount of solvent contained in the charge generating layer immediately before forming the charge transport layer is 0.1 ppm or more and 500 ppm or less; The distance Ra between the HSP of a solvent contained in the charge generating layer immediately before the formation of the charge transport layer and the HSP of a binder resin contained in the coating liquid for forming the charge transport layer is 8 or more and 10 or less. HSP is the Hansen Solubility Parameter.
[0022] According to the manufacturing method of the present embodiment, an electrophotographic photoreceptor having a photosensitive layer with excellent thickness uniformity can be manufactured with good productivity. The mechanism behind this is assumed to be as follows. In the following description, the charge generating layer is referred to as a "CG layer" and the charge transport layer is referred to as a "CT layer."
[0023] It is known that the thickness of a coating film formed by dip coating depends on the withdrawal speed and the physical properties of the coating liquid, and is expressed by the following formula (1). Equation (1): t = k√(vη / ρg) t: thickness of coating film k: coefficient v: pulling speed η: Viscosity of coating liquid ρ: Density of coating liquid g:Gravity acceleration From the viewpoint of increasing the production line speed and improving productivity, it is desirable for the pulling speed v to be high. From the viewpoint of uniformity of the formed film, it is desirable to have a short time required for drying the coated film, and therefore it is desirable for the coating liquid to have a large solid content, in which case the viscosity η of the coating liquid increases (because the viscosity η of the coating liquid is directly correlated with the solid content of the coating liquid). Both of the above factors act in the direction of increasing the thickness t of the coating film. If the thickness t of the coating film is to be kept within a specified range, it is not possible to increase both of the above two factors at the same time; increasing one of them requires decreasing the other. Furthermore, if the viscosity η of the coating solution (i.e., the solid content of the coating solution) is increased, the thickness t of the coating film can be made relatively thinner to obtain a dried film of a specified thickness, so the pulling speed v must be slowed down to reduce the thickness t of the coating film. For the above reasons, there is a trade-off between the pulling speed v and the viscosity η of the coating liquid, and therefore it is difficult to improve both the productivity and the film formation uniformity at the same time.
[0024] As a result of the inventors of the present disclosure studying the formation of the CT layer, it was found that the interface state between the CG layer and the CT layer coating liquid is a factor that reduces the thickness of the CT layer coating film. This factor is presumed to be the phenomenon (called the "slip phenomenon") that causes the CT layer coating liquid to slide and fall in the direction of gravity at the interface between the CG layer and the CT layer coating liquid. Introducing the effect of this factor into formula (1) can be expressed as the following formula (2). In formula (2), "-f" means thinning due to the slip phenomenon. Equation (2): t = k√(vη / ρg)-f When slippage occurs at the interface between the CG layer and the CT layer coating liquid, even if the pulling speed v and / or the viscosity η of the coating liquid are increased, the thickness t of the coating film can be kept within a specified range because "-f" in formula (2) (thinning due to slippage) is offset. In other words, the pulling speed v and / or the viscosity η of the coating liquid can be increased to compensate for "-f" (thinning due to slippage). Therefore, both the productivity and the film formation uniformity can be improved while maintaining the thickness t of the coating film and the film thickness after drying within a specified range.
[0025] As a result of research conducted by the inventors of the present disclosure, an effect presumably due to the slip phenomenon was observed when the amount of residual solvent in the CG layer when the CT layer was formed was 0.1 ppm or more and 500 ppm or less, and the distance Ra between the HSP of the residual solvent in the CG layer and the HSP of the binder resin in the CT layer coating solution was 8 or more and 10 or less. It is presumed that if the amount of residual solvent in the CG layer is less than 0.1 ppm or the distance Ra exceeds 10, the surface of the CG layer is hardly dissolved in the CT layer coating liquid, and therefore the slip phenomenon does not occur. If the amount of residual solvent in the CG layer exceeds 500 ppm or the distance Ra is less than 8, the surface of the CG layer will dissolve excessively, and the CT layer coating liquid will get caught on the exposed charge generating material (generally pigment particles) of the CG layer, preventing the slip phenomenon from occurring. Conversely, it is presumed that the CT layer coating liquid will be less likely to fall in the direction of gravity. In order for the surface of the CG layer to be appropriately dissolved to cause a slip phenomenon, the amount of residual solvent in the CG layer is 0.1 ppm or more and 500 ppm or less relative to the mass of the CG layer, and the distance Ra is 8 or more and 10 or less.
[0026] The amount of residual solvent in the CG layer is, from the viewpoint of allowing the surface of the CG layer to dissolve moderately and causing a slip phenomenon, from 0.1 ppm to 500 ppm, preferably from 10 ppm to 300 ppm, and more preferably from 50 ppm to 150 ppm, relative to the mass of the CG layer.
[0027] The distance Ra between the HSP of the residual solvent in the CG layer and the HSP of the binder resin in the CT layer coating solution is, from the viewpoint of adequately dissolving the surface of the CG layer and causing a slip phenomenon, 8 or more and 10 or less, preferably 8.5 or more and 9.5 or less, and more preferably 8.8 or more and 9.3 or less.
[0028] The amount of the solvent contained in the charge generating layer is determined using a gas chromatograph-mass spectrometer. A solvent to be used in preparing a coating liquid for forming a charge generating layer is prepared in advance, and the retention time when the solvent is heated and vaporized at 300° C. is measured, and a calibration curve including a range of 0.05 ppm to 1500 ppm is prepared. The charge generating layer is peeled off from the conductive substrate, cut into a 1 cm x 1 cm square, and precisely weighed. This square charge generating layer is placed in a vial and heated at 300°C, and the retention time of the volatile components is measured. The amount of solvent is calculated based on the peak area of the corresponding component that appears in the chromatograph and the calibration curve. The mass percentage (ppm) of the solvent in the 1 cm x 1 cm charge generating layer is calculated.
[0029] The amount of solvent contained in the charge generating layer immediately before forming the charge transport layer can be adjusted by the drying temperature of the coating film when forming the charge generating layer by coating. The drying temperature of the coating film is adjusted according to the boiling point of the solvent used in preparing the coating liquid for forming the charge generating layer so that the amount of solvent contained in the charge generating layer after drying is 0.1 ppm or more and 500 ppm or less.
[0030] In this embodiment, the Hansen solubility parameter (HSP) is a value at a temperature of 25° C. (298.15 K). For HSP, values listed in "Hansen Solubility Parameters: A User's Handbook, Second Edition" are used. For chemical substances not listed, calculations are performed using the software "Hansen Solubility Parameter in Practice (HSPiP) Ver5.202." HSP consists of three components: the dispersion force term δd, the dipole-dipole force term δp, and the hydrogen bond force term δh. The units of all three components are MPa. 0.5 It is. The HSP of a mixed solvent is a weighted average of the mass ratio. For example, solvent A (δd A , δp A , δh A ) and solvent B (δd B , δp B , δh B The HSP of a mixed solvent of 1:1 with (0.5 δd A +0.5 δd B , 0.5·δp A +0.5 δp B ,0.5·δh A +0.5 δh B ). The distance Ra between solvent 1 (δd1, δp1, δh1) and solvent 2 (δd2, δp2, δh2) in the HSP space is given by the following formula. Ra = √{4(δd2-δd1) 2 +(δp2-δp1) 2 +(δh2-δh1) 2}
[0031] Each layer of the photoreceptor and the method of forming the same will now be described in detail.
[0032] [Conductive substrate] Examples of conductive substrates include metal plates, metal drums, and metal belts containing metals (aluminum, copper, zinc, chromium, nickel, molybdenum, vanadium, indium, gold, platinum, etc.) or alloys (stainless steel, etc.). Examples of conductive substrates also include paper, resin films, belts, etc., onto which a conductive compound (e.g., conductive polymer, indium oxide, etc.), a metal (e.g., aluminum, palladium, gold, etc.) or an alloy is applied, vapor-deposited, or laminated. Here, "conductive" refers to a material having a volume resistivity of 1×10 13 This means that the resistance is less than Ωcm.
[0033] When the electrophotographic photoreceptor is used in a laser printer, the surface of the conductive substrate is preferably roughened to a center line average roughness Ra of 0.04 μm to 0.5 μm in order to suppress interference fringes that occur when irradiating with laser light. When non-interfering light is used as the light source, roughening to prevent interference fringes is not particularly necessary, but it is suitable for extending the life of the conductive substrate since it suppresses the occurrence of defects due to unevenness on the surface.
[0034] Examples of methods for roughening the surface include wet honing, which involves spraying an abrasive suspended in water onto the conductive substrate; centerless grinding, in which the conductive substrate is pressed against a rotating grindstone and continuously ground; and anodizing.
[0035] As a method for roughening the surface, there can be mentioned a method in which, without roughening the surface of the conductive substrate, a conductive or semiconductive powder is dispersed in a resin to form a layer on the surface of the conductive substrate, and the surface is roughened by the particles dispersed in the layer.
[0036] In the roughening treatment by anodization, an oxide film is formed on the surface of a conductive substrate made of metal (e.g., aluminum) by anodizing the substrate in an electrolyte solution using the substrate as the anode. Examples of electrolyte solutions include sulfuric acid solution and oxalic acid solution. However, the porous anodic oxide film formed by anodization is chemically active in its original state, easily contaminated, and has a large resistance variation depending on the environment. Therefore, it is preferable to perform a sealing treatment on the porous anodic oxide film, in which the micropores of the oxide film are filled by volume expansion caused by hydration reaction in pressurized steam or boiling water (metal salts such as nickel may be added) to change the film into a more stable hydrated oxide.
[0037] The thickness of the anodic oxide film is preferably, for example, from 0.3 μm to 15 μm. If the thickness is within this range, the film tends to exhibit a barrier property against injection and tends to suppress an increase in residual potential due to repeated use.
[0038] The conductive substrate may be subjected to a treatment with an acidic treatment solution or a boehmite treatment. Treatment with an acid treatment liquid is carried out, for example, as follows. First, an acid treatment liquid containing phosphoric acid, chromic acid, and hydrofluoric acid is prepared. The compounding ratios of phosphoric acid, chromic acid, and hydrofluoric acid in the acid treatment liquid are, for example, in the range of 10% by mass to 11% by mass for phosphoric acid, 3% by mass to 5% by mass for chromic acid, and 0.5% by mass to 2% by mass for hydrofluoric acid, and the total concentration of these acids is preferably in the range of 13.5% by mass to 18% by mass. The treatment temperature is preferably, for example, 42° C. to 48° C. The film thickness of the coating is preferably 0.3 μm to 15 μm.
[0039] The boehmite treatment is carried out, for example, by immersing the material in pure water at 90° C. to 100° C. for 5 to 60 minutes, or by contacting the material with heated steam at 90° C. to 120° C. for 5 to 60 minutes. The thickness of the coating is preferably 0.1 μm to 5 μm. This may be further anodized using an electrolyte solution having low coating solubility, such as adipic acid, boric acid, borates, phosphates, phthalates, maleates, benzoates, tartrates, or citrates.
[0040] [Sublayer] The undercoat layer is, for example, a layer containing inorganic particles and a binder resin.
[0041] For example, inorganic particles have a powder resistance (volume resistivity) of 1×10 2 Ωcm or more 1×10 11 Examples of inorganic particles having a resistance value of Ωcm or less include metal oxide particles such as tin oxide particles, titanium oxide particles, zinc oxide particles, zirconium oxide particles, and zinc oxide particles are particularly preferred.
[0042] The specific surface area of inorganic particles by the BET method is, for example, 10 m 2 / g or higher is preferable. The volume average particle size of the inorganic particles is, for example, from 50 nm to 2000 nm (preferably from 60 nm to 1000 nm).
[0043] The content of the inorganic particles is, for example, preferably from 10% by mass to 80% by mass, more preferably from 40% by mass to 80% by mass, based on the binder resin.
[0044] The inorganic particles may be surface-treated. Two or more types of inorganic particles having different surface treatments or different particle sizes may be used in combination.
[0045] Examples of the surface treatment agent include a silane coupling agent, a titanate coupling agent, an aluminum coupling agent, a surfactant, etc. In particular, a silane coupling agent is preferred, and a silane coupling agent having an amino group is more preferred.
[0046] Examples of silane coupling agents having an amino group include, but are not limited to, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.
[0047] Silane coupling agents may be used in combination of two or more kinds. For example, a silane coupling agent having an amino group may be used in combination with another silane coupling agent. Examples of other silane coupling agents include, but are not limited to, vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
[0048] The surface treatment method using the surface treatment agent may be any known method, and may be either a dry method or a wet method.
[0049] The amount of the surface treatment agent to be used is preferably, for example, 0.5% by mass or more and 10% by mass or less based on the inorganic particles.
[0050] The undercoat layer preferably contains an electron-accepting compound (acceptor compound) together with inorganic particles, from the viewpoints of improving the long-term stability of electrical properties and carrier blocking properties.
[0051] Examples of the electron-accepting compound include electron-transporting substances such as quinone compounds such as chloranil and bromoanil; tetracyanoquinodimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone and 2,4,5,7-tetranitro-9-fluorenone; oxadiazole compounds such as 2-(4-biphenyl)-5-(4-t-butylphenyl)-1,3,4-oxadiazole, 2,5-bis(4-naphthyl)-1,3,4-oxadiazole and 2,5-bis(4-diethylaminophenyl)-1,3,4-oxadiazole; xanthone compounds; thiophene compounds; and diphenoquinone compounds such as 3,3',5,5'-tetra-t-butyldiphenoquinone. In particular, the electron-accepting compound is preferably a compound having an anthraquinone structure. Examples of the compound having an anthraquinone structure include hydroxyanthraquinone compounds, aminoanthraquinone compounds, and aminohydroxyanthraquinone compounds, and more specifically, anthraquinone, alizarin, quinizarin, anthrarufin, and purpurin.
[0052] The electron accepting compound may be contained in the undercoat layer in a dispersed state together with the inorganic particles, or may be contained in a state of being attached to the surfaces of the inorganic particles.
[0053] The method for attaching the electron accepting compound to the surface of the inorganic particles may be, for example, a dry method or a wet method.
[0054] The dry method is, for example, a method in which an electron-accepting compound is attached to the surface of inorganic particles by dropping an electron-accepting compound directly or dissolved in an organic solvent or spraying it together with dry air or nitrogen gas while stirring inorganic particles with a mixer or the like that exerts a large shearing force. The dropping or spraying of the electron-accepting compound is preferably performed at a temperature below the boiling point of the solvent. After dropping or spraying the electron-accepting compound, baking may be performed at 100° C. or higher. The temperature and time of baking are not particularly limited as long as electrophotographic properties can be obtained.
[0055] The wet method is a method in which, for example, an electron-accepting compound is added while dispersing inorganic particles in a solvent by stirring, ultrasonic waves, a sand mill, an attritor, a ball mill, etc., and the inorganic particles are stirred or dispersed, and then the solvent is removed to attach the electron-accepting compound to the surface of the inorganic particles. The solvent is removed, for example, by filtration or distillation. After the solvent is removed, baking may be performed at 100°C or higher. The baking temperature and time are not particularly limited as long as electrophotographic properties are obtained. In the wet method, moisture contained in the inorganic particles may be removed before adding the electron-accepting compound, and examples of such methods include a method of removing the moisture while stirring and heating in a solvent, and a method of removing the moisture by azeotropy with the solvent.
[0056] The attachment of the electron accepting compound may be carried out before or after the inorganic particles are subjected to a surface treatment with a surface treatment agent, or the attachment of the electron accepting compound and the surface treatment with the surface treatment agent may be carried out simultaneously.
[0057] The content of the electron accepting compound is, for example, from 0.01% by mass to 20% by mass, and preferably from 0.01% by mass to 10% by mass, based on the inorganic particles.
[0058] Examples of the binder resin used in the undercoat layer include known materials such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, unsaturated polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, alkyd resins, and epoxy resins; zirconium chelate compounds; titanium chelate compounds; aluminum chelate compounds; titanium alkoxide compounds; organic titanium compounds; and silane coupling agents. Examples of the binder resin used in the undercoat layer include charge transporting resins having charge transporting groups, conductive resins (such as polyaniline, etc.), and the like.
[0059] Among these, the binder resin used in the undercoat layer is preferably a resin that is insoluble in the coating solvent of the upper layer, and in particular, a resin obtained by reacting at least one resin selected from the group consisting of thermosetting resins such as urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, unsaturated polyester resins, alkyd resins, and epoxy resins, with a curing agent is preferred. When two or more of these binder resins are used in combination, the mixing ratio is set as necessary.
[0060] The undercoat layer may contain various additives for improving electrical properties, environmental stability, and image quality. Examples of the additives include known materials such as polycyclic condensation and azo-based electron transport pigments, zirconium chelate compounds, titanium chelate compounds, aluminum chelate compounds, titanium alkoxide compounds, organic titanium compounds, silane coupling agents, etc. As described above, silane coupling agents are used for surface treatment of inorganic particles, and may also be added to the undercoat layer as an additive.
[0061] Examples of silane coupling agents as additives include vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, and the like.
[0062] Examples of the zirconium chelate compound include zirconium butoxide, zirconium ethyl acetoacetate, zirconium triethanolamine, acetylacetonate zirconium butoxide, ethyl acetoacetate zirconium butoxide, zirconium acetate, zirconium oxalate, zirconium lactate, zirconium phosphonate, zirconium octanoate, zirconium naphthenate, zirconium laurate, zirconium stearate, zirconium isostearate, methacrylate zirconium butoxide, stearate zirconium butoxide, and isostearate zirconium butoxide.
[0063] Examples of titanium chelate compounds include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, titanium acetylacetonate, polytitanium acetylacetonate, titanium octylene glycolate, titanium lactate ammonium salt, titanium lactate, titanium lactate ethyl ester, titanium triethanolamine, and polyhydroxytitanium stearate.
[0064] Examples of aluminum chelate compounds include aluminum isopropylate, monobutoxyaluminum diisopropylate, aluminum butyrate, diethylacetoacetate aluminum diisopropylate, and aluminum tris(ethylacetoacetate).
[0065] These additives may be used alone or as a mixture or polycondensation product of a plurality of compounds.
[0066] The undercoat layer preferably has a Vickers hardness of 35 or more. The surface roughness (ten-point average roughness) of the undercoat layer is preferably adjusted to between 1 / (4n) (n is the refractive index of the upper layer) and 1 / 2 of the wavelength λ of the exposure laser used in order to suppress moire images. Resin particles or the like may be added to the undercoat layer to adjust the surface roughness. Examples of the resin particles include silicone resin particles and crosslinked polymethyl methacrylate resin particles. The surface of the undercoat layer may be polished to adjust the surface roughness. Examples of the polishing method include buffing, sandblasting, wet honing, grinding, and the like.
[0067] The formation of the undercoat layer is not particularly limited, and a known formation method can be used. For example, the undercoat layer can be formed by forming a coating film of a coating solution for forming the undercoat layer in which the above-mentioned components are added to a solvent, drying the coating film, and heating it as necessary.
[0068] Examples of the solvent for preparing the coating liquid for forming the undercoat layer include known organic solvents, such as alcohol-based solvents, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, ketone-based solvents, ketone alcohol-based solvents, ether-based solvents, and ester-based solvents. Specific examples of these solvents include ordinary organic solvents such as methanol, ethanol, n-propanol, iso-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, and toluene.
[0069] Examples of the method for dispersing the inorganic particles when preparing the coating liquid for forming the undercoat layer include known methods such as those using a roll mill, a ball mill, a vibrating ball mill, an attritor, a sand mill, a colloid mill, and a paint shaker.
[0070] Examples of the method for applying the coating liquid for forming the undercoat layer onto the conductive substrate include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0071] The thickness of the undercoat layer is set, for example, preferably at least 15 μm, and more preferably within the range of from 20 μm to 50 μm.
[0072] [Middle layer] An intermediate layer may further be provided between the undercoat layer and the photosensitive layer. The intermediate layer is, for example, a layer containing a resin. Examples of the resin used in the intermediate layer include polymer compounds such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, phenol-formaldehyde resins, and melamine resins. The intermediate layer may be a layer containing an organometallic compound. Examples of the organometallic compound used in the intermediate layer include organometallic compounds containing metal atoms such as zirconium, titanium, aluminum, manganese, and silicon. The compounds used in the intermediate layer may be used alone or as a mixture or polycondensation product of a plurality of compounds.
[0073] Among these, the intermediate layer is preferably a layer containing an organometallic compound containing zirconium atoms or silicon atoms.
[0074] The formation of the intermediate layer is not particularly limited, and a known formation method can be used. For example, the intermediate layer can be formed by forming a coating film of a coating solution for forming an intermediate layer in which the above components are added to a solvent, drying the coating film, and heating it as necessary. The intermediate layer can be formed by any of the usual coating methods, such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating and curtain coating.
[0075] The thickness of the intermediate layer is preferably set in the range of, for example, 0.1 μm to 3 μm The intermediate layer may be used as an undercoat layer.
[0076] [Charge generation layer] The charge generating layer is, for example, a layer containing a charge generating material and a binder resin.
[0077] Examples of the charge generating material include azo pigments such as bisazo and trisazo; condensed aromatic pigments such as dibromoanthanthrone; perylene pigments; pyrrolopyrrole pigments; phthalocyanine pigments; zinc oxide; and trigonal selenium.
[0078] Among these, in order to accommodate laser exposure in the near infrared region, it is preferable to use a metal phthalocyanine pigment or a metal-free phthalocyanine pigment as the charge generating material. Specifically, at least one selected from the group consisting of hydroxygallium phthalocyanine, chlorogallium phthalocyanine, dichlorotin phthalocyanine, and titanyl phthalocyanine is preferable, hydroxygallium phthalocyanine and / or chlorogallium phthalocyanine is more preferable, and hydroxygallium phthalocyanine is even more preferable.
[0079] On the other hand, in order to accommodate laser exposure in the near ultraviolet region, preferred charge generating materials include condensed aromatic pigments such as dibromoanthanthrone, thioindigo pigments, porphyrazine compounds, zinc oxide, trigonal selenium, and bisazo pigments.
[0080] The above charge generating materials may be used when using incoherent light sources such as LEDs and organic EL image arrays that emit light at a central wavelength of 450 nm to 780 nm, but from the viewpoint of resolution, when using a thin photosensitive layer of 20 μm or less, the electric field strength in the photosensitive layer becomes high, and a decrease in charging due to charge injection from the substrate, so-called black spots, is likely to occur as an image defect. This becomes more noticeable when using charge generating materials that are p-type semiconductors such as trigonal selenium and phthalocyanine pigments and are prone to generating dark current.
[0081] In contrast, when n-type semiconductors such as fused aromatic pigments, perylene pigments, and azo pigments are used as charge generating materials, dark current is unlikely to occur, and image defects called black spots can be suppressed even in thin films. The n-type is determined by the polarity of the flowing photocurrent using the commonly used time-of-flight method, and those that are more likely to pass electrons as carriers than holes are considered to be n-type.
[0082] The binder resin used in the charge generating layer may be selected from a wide range of insulating resins, and may also be selected from organic photoconductive polymers such as poly-N-vinylcarbazole, polyvinylanthracene, polyvinylpyrene, polysilane, and the like. Examples of binder resins include polyvinyl butyral resins, polyarylate resins (polycondensates of bisphenols and aromatic dicarboxylic acids, etc.), polycarbonate resins, polyester resins, phenoxy resins, vinyl chloride-vinyl acetate copolymers, polyamide resins, acrylic resins, polyacrylamide resins, polyvinylpyridine resins, cellulose resins, urethane resins, epoxy resins, casein, polyvinyl alcohol resins, polyvinylpyrrolidone resins, etc. Here, "insulating" refers to a material having a volume resistivity of 1×10 13 This means that the resistance is Ωcm or more. These binder resins may be used alone or in combination of two or more.
[0083] The compounding ratio of the charge generating material to the binder resin is preferably within a range of 10:1 to 1:10 by mass.
[0084] The charge generating layer may contain other known additives.
[0085] The charge generation layer is formed by coating. An embodiment of the coating method includes, for example, dissolving or dispersing the above-mentioned components in a solvent to prepare a coating liquid for forming a charge generation layer, coating the coating liquid for forming a charge generation layer on the surface of a conductive substrate, the surface of an undercoat layer, or the surface of an intermediate layer to form a coating film, and drying the coating film.
[0086] Examples of the solvent for preparing the coating liquid for forming the charge generating layer include methanol, ethanol, n-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, toluene, etc. These solvents may be used alone or in combination of two or more.
[0087] Examples of methods for dispersing particles (e.g., charge generating material) in the coating liquid for forming a charge generating layer include media dispersers such as ball mills, vibration ball mills, attritors, sand mills, and horizontal sand mills, and medialess dispersers such as stirrers, ultrasonic dispersers, roll mills, and high-pressure homogenizers. Examples of high-pressure homogenizers include a collision method in which the dispersion liquid is dispersed by liquid-liquid collision or liquid-wall collision under high pressure, and a penetration method in which the dispersion liquid is dispersed by penetrating a fine flow path under high pressure. During this dispersion, it is effective to adjust the average particle size of the charge generating material in the coating liquid for forming the charge generating layer to 0.5 μm or less, preferably 0.3 μm or less, and more preferably 0.15 μm or less.
[0088] Examples of a method for applying the coating liquid for forming the charge generating layer onto the undercoat layer (or onto the intermediate layer) include conventional methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0089] The drying temperature of the coating film is adjusted according to the boiling point of the solvent used in preparing the coating liquid for forming the charge generating layer so that the amount of solvent contained in the dried charge generating layer is 0.1 ppm or more and 500 ppm or less. When the boiling point of the solvent with the lowest boiling point among the solvents used in preparing the coating solution is BP1°C, and the boiling point of the solvent with the highest boiling point is BP2°C (if there is only one type of solvent, BP1 = BP2), the drying temperature of the coating film is preferably (BP1-30)°C or more and (BP2+30)°C or less, more preferably (BP1-20)°C or more and (BP2+20)°C or less, and even more preferably (BP1-10)°C or more and (BP2+10)°C or less.
[0090] The thickness of the charge generating layer is set, for example, preferably in the range of 0.1 μm or more and 5.0 μm or less, and more preferably in the range of 0.2 μm or more and 2.0 μm or less.
[0091] [Charge transport layer] The charge transport layer is, for example, a layer containing a charge transport material and a binder resin, and may be a layer containing a polymer charge transport material.
[0092] Examples of the charge transport material include electron transporting compounds such as quinone compounds such as p-benzoquinone, chloranil, bromanil, and anthraquinone; tetracyanoquinodimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone; xanthone compounds; benzophenone compounds; cyanovinyl compounds; and ethylene compounds. Examples of the charge transport material include hole transporting compounds such as triarylamine compounds, benzidine compounds, arylalkane compounds, aryl-substituted ethylene compounds, stilbene compounds, anthracene compounds, and hydrazone compounds. These charge transport materials may be used alone or in combination, but are not limited to these.
[0093] As the charge transport material, from the viewpoint of charge mobility, a triarylamine derivative represented by the following structural formula (a-1) and a benzidine derivative represented by the following structural formula (a-2) are preferable.
[0094] [ka]
[0095] In structural formula (a-1), Ar T1 , Ar T2 , and Ar T3 each independently represents a substituted or unsubstituted aryl group, -C6H4-C(R T4 )=C(R T5 )(R T6 ), or -CH-CH=CH-CH=C(R T7 )(R T8 ) is shown. T4 , R T5 , R T6 , R T7 , and R T8 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.
[0096] [ka]
[0097] In structural formula (a-2), R T91 and R T92 R each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms. T101 , R T102 , R T111 and R T112 each independently represents a halogen atom, an alkyl group having from 1 to 5 carbon atoms, an alkoxy group having from 1 to 5 carbon atoms, an amino group substituted with an alkyl group having from 1 to 2 carbon atoms, a substituted or unsubstituted aryl group, -C(R T12 )=C(R T13 )(R T14 ), or -CH=CH-CH=C(R T15 )(R T16 ) and R T12 , R T13 , R T14 , R T15 and R T16 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Tm1, Tm2, Tn1, and Tn2 each independently represent an integer of 0 or more and 2 or less. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.
[0098] Among the triarylamine derivatives represented by the structural formula (a-1) and the benzidine derivatives represented by the structural formula (a-2), in particular, "-C6H4-CH=CH-CH=C(R T7)(R T8 )" and triarylamine derivatives having "-CH=CH-CH=C(R T15 )(R T16 ) is preferable from the viewpoint of charge mobility.
[0099] As the polymer charge transport material, known materials having charge transport properties such as poly-N-vinylcarbazole and polysilane are used. In particular, polyester polymer charge transport materials are particularly preferred. The polymer charge transport material may be used alone or in combination with a binder resin.
[0100] Examples of the binder resin used in the charge transport layer include polycarbonate resin, polyester resin, polyarylate resin, methacrylic resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, styrene-butadiene copolymer, vinylidene chloride-acrylonitrile copolymer, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, styrene-alkyd resin, poly-N-vinylcarbazole, polysilane, etc. Among these, polycarbonate resin or polyarylate resin is suitable as the binder resin. These binder resins are used alone or in combination of two or more. The compounding ratio of the charge transport material to the binder resin is preferably from 10:1 to 1:5 by mass.
[0101] The binder resin of the charge transport layer preferably contains a polyarylate resin, which improves the abrasion resistance of the charge transport layer by binding resin molecules to each other through intermolecular forces due to stacking of aromatic rings.
[0102] The dicarboxylic acid constituting the polyarylate resin preferably contains at least one selected from the group consisting of biphenyldicarboxylic acid and methyl-substituted biphenyldicarboxylic acid, and more preferably contains 4,4'-biphenyldicarboxylic acid. The diphenol constituting the polyarylate resin preferably contains bisphenols, and 4,4'-CR 1 R 2 -Diphenol (R 1 and R 2 are each independently a saturated hydrocarbon group having 1 to 6 carbon atoms, R 1 and R 2 may be linked to form a ring.) It is more preferable that the 4,4'-CR 1 R 2 -Diphenol-CR 1 R 2 The - preferably has a total carbon number of 10 or less, more preferably 8 or less, and even more preferably 6 or less.
[0103] The weight average molecular weight of the polyarylate resin is preferably 50,000 or more, more preferably 80,000 or more, and even more preferably 100,000 or more, from the viewpoint of the abrasion resistance of the charge transport layer. The weight average molecular weight of the polyarylate resin is preferably 300,000 or less, more preferably 250,000 or less, and even more preferably 200,000 or less, from the viewpoint of ensuring a certain level of polyarylate resin concentration in the coating liquid for forming the charge transport layer. The molecular weight of the polyarylate resin is a polystyrene-equivalent molecular weight measured by gel permeation chromatography (GPC), which uses tetrahydrofuran as an eluent.
[0104] The proportion of the polyarylate resin in the total amount of the binder resin contained in the charge transport layer is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.
[0105] The charge transport layer may contain other known additives.
[0106] The charge transport layer is formed by dip coating. An embodiment of the dip coating includes, for example, dissolving or dispersing the above-mentioned components in a solvent to prepare a coating liquid for forming a charge transport layer, dip-coating the coating liquid for forming a charge transport layer on the surface of the charge generating layer to form a coating film, and drying the coating film.
[0107] From the viewpoint of the balance between the production line speed and the film formation uniformity, the viscosity of the coating solution for forming the charge transport layer is preferably from 500 mPa·S to 1000 mPa·S, more preferably from 600 mPa·S to 950 mPa·S, and even more preferably from 700 mPa·S to 900 mPa·S. The viscosity of the coating liquid for forming the charge transport layer is preferably 1000 mPa·S or less, more preferably 950 mPa·S or less, and even more preferably 900 mPa·S or less, from the viewpoint of easily causing the phenomenon (referred to as the "slip phenomenon") in which the coating liquid for forming the charge transport layer slides and falls in the direction of gravity at the interface between the charge generating layer and the coating liquid for forming the charge transport layer.
[0108] The pull-up speed when dip-coating the charge transport layer is preferably 100 mm / min to 200 mm / min, more preferably 120 mm / min to 180 mm / min, and even more preferably 130 mm / min to 170 mm / min, from the viewpoint of the balance between the production line speed and the film formation uniformity.
[0109] Examples of solvents for preparing the coating liquid for forming the charge transport layer include ordinary organic solvents such as aromatic hydrocarbons such as benzene, toluene, xylene, and chlorobenzene, ketones such as acetone and 2-butanone, halogenated aliphatic hydrocarbons such as methylene chloride, chloroform, and ethylene chloride, and cyclic or linear ethers such as tetrahydrofuran and ethyl ether. These solvents may be used alone or in combination of two or more.
[0110] Examples of a coating method for coating the coating liquid for forming the charge transport layer on the charge generating layer include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating and curtain coating.
[0111] From the viewpoint of extending the life of the photoreceptor, the thickness of the charge transport layer is preferably 30 μm or more, more preferably 35 μm or more, and even more preferably 38 μm or more. The thickness of the charge transport layer is preferably 50 μm or less, more preferably 48 μm or less, and even more preferably 45 μm or less, from the viewpoint of suppressing unevenness in the thickness of the charge transport layer and thereby suppressing unevenness in image density. The thickness of the charge transport layer is the arithmetic average of values measured by an electromagnetic film thickness meter, and the measurement points are four points at 90° intervals in the circumferential direction from the center in the axial direction of the photoreceptor.
[0112] [Protective layer] A protective layer is provided on the photosensitive layer as necessary for the purpose of, for example, preventing chemical changes in the photosensitive layer when the photosensitive layer is charged and further improving the mechanical strength of the photosensitive layer. Therefore, it is preferable to apply a layer composed of a cured film (crosslinked film) as the protective layer. Examples of such a layer include the following layers 1) and 2).
[0113] 1) A layer composed of a cured film of a composition containing a reactive group-containing charge transport material having a reactive group and a charge transport skeleton in the same molecule (i.e., a layer containing a polymer or crosslinked product of the reactive group-containing charge transport material). 2) A layer composed of a cured film of a composition containing a non-reactive charge transport material and a reactive group-containing non-charge transport material that does not have a charge transport skeleton and has a reactive group (i.e., a layer containing a non-reactive charge transport material and a polymer or crosslinked body of the reactive group-containing non-charge transport material).
[0114] The reactive group of the reactive group-containing charge transport material may be a chain polymerizable group, an epoxy group, -OH, -OR (wherein R represents an alkyl group), -NH2, -SH, -COOH, or -SiR. Q1 3-Qn (OR Q2 ) Qn [However, R Q1 represents a hydrogen atom, an alkyl group, or a substituted or unsubstituted aryl group; R Q2 represents a hydrogen atom, an alkyl group, or a trialkylsilyl group; Qn represents an integer of 1 to 3.
[0115] The chain polymerizable group is not particularly limited as long as it is a functional group capable of radical polymerization, and is, for example, a functional group having a group containing at least a carbon double bond.Specific examples include a group containing at least one selected from a vinyl group, a vinyl ether group, a vinyl thioether group, a styryl group (vinyl phenyl group), an acryloyl group, a methacryloyl group, and derivatives thereof.Among them, the chain polymerizable group is preferably a group containing at least one selected from a vinyl group, a styryl group (vinyl phenyl group), an acryloyl group, a methacryloyl group, and derivatives thereof, because of its excellent reactivity.
[0116] The charge transporting skeleton of the reactive group-containing charge transporting material is not particularly limited as long as it is a known structure in electrophotographic photoreceptors, and examples thereof include a skeleton derived from a nitrogen-containing hole transporting compound such as a triarylamine compound, a benzidine compound, a hydrazone compound, etc., and a structure conjugated with a nitrogen atom. Among these, a triarylamine skeleton is preferred.
[0117] The reactive group-containing charge transport material having a reactive group and a charge transporting skeleton, the non-reactive charge transport material, and the reactive group-containing non-charge transport material may be selected from well-known materials.
[0118] The protective layer may contain other well-known additives.
[0119] The formation of the protective layer is not particularly limited, and a well-known formation method can be used. For example, the protective layer can be formed by forming a coating film of a coating liquid for forming the protective layer in which the above components are added to a solvent, drying the coating film, and, if necessary, subjecting it to a curing treatment such as heating.
[0120] Examples of solvents for preparing a coating solution for forming a protective layer include aromatic solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, ester solvents such as ethyl acetate and butyl acetate, ether solvents such as tetrahydrofuran and dioxane, cellosolve solvents such as ethylene glycol monomethyl ether, and alcohol solvents such as isopropyl alcohol and butanol. These solvents may be used alone or in combination of two or more. The coating liquid for forming the protective layer may be a solvent-free coating liquid.
[0121] Examples of a method for applying the protective layer-forming coating liquid onto a photosensitive layer (e.g., a charge transport layer) include conventional methods such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating, and curtain coating.
[0122] The thickness of the protective layer is set, for example, preferably in the range of 1 μm or more and 20 μm or less, and more preferably in the range of 2 μm or more and 10 μm or less. EXAMPLES
[0123] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are by mass. In the following description, unless otherwise specified, synthesis, production, processing, measurement, etc. were carried out at room temperature (25° C.±3° C.).
[0124] <Example 1> [Formation of undercoat layer] As a conductive substrate, an aluminum cylindrical tube having an outer diameter of 30 mm, a length of 365 mm, and a wall thickness of 2 mm was prepared.
[0125] Zinc oxide (average particle size 70 nm, specific surface area 15 m 2100 parts of a silane coupling agent (trade name: KBM603, Shin-Etsu Chemical Co., Ltd., N-2-(aminoethyl)-3-aminopropyltrimethoxysilane) was added and stirred for 2 hours. The toluene was then distilled off under reduced pressure, and the mixture was baked at 120°C for 3 hours to obtain zinc oxide surface-treated with the silane coupling agent.
[0126] 110 parts of the surface-treated zinc oxide was mixed with 500 parts of tetrahydrofuran by stirring, and a solution of 0.6 parts of alizarin dissolved in 50 parts of tetrahydrofuran was added thereto, followed by stirring for 5 hours at 50° C. Next, the solid content was filtered off by reduced pressure filtration and dried under reduced pressure at 60° C. to obtain zinc oxide with alizarin added thereto.
[0127] 100 parts of a solution of 60 parts of alizarin-added zinc oxide, 13.5 parts of a curing agent (blocked isocyanate, product name: Sumidur 3175, Sumitomo Bayer Urethane Co., Ltd.), and 15 parts of butyral resin (product name: S-LEC BM-1, Sekisui Chemical Co., Ltd.) dissolved in 68 parts of methyl ethyl ketone was mixed with 5 parts of methyl ethyl ketone, and dispersed for 2 hours in a sand mill using glass beads with a diameter of 1 mm to obtain a dispersion. 0.005 parts of dioctyltin dilaurate as a catalyst and 4 parts of silicone resin particles (product name: Tospearl 145, Momentive Performance Materials Co., Ltd.) were added to the dispersion to obtain a coating liquid for forming an undercoat layer. The coating liquid for forming an undercoat layer was applied to the outer peripheral surface of a conductive substrate by dip coating, and dried and cured at 170°C for 40 minutes to form an undercoat layer with a thickness of 20 μm.
[0128] [Formation of charge generation layer] Charge generating material: Hydroxygallium phthalocyanine 3 parts Binder resin: Vinyl chloride / vinyl acetate copolymer 2 parts Solvent: n-Butyl acetate 66.5 parts Solvent: 28.5 parts methyl isobutyl ketone The above materials were mixed and dispersed in a sand mill using glass beads with a diameter of 1 mm for 4 hours to obtain a coating solution for forming a charge generation layer. The coating solution for forming a charge generation layer was dip-coated on the undercoat layer and dried at a temperature of 110°C to form a charge generation layer with a layer thickness of 0.2 μm.
[0129] [Formation of charge transport layer] Binder resin: Polyarylate resin (1) (weight average molecular weight 110,000)... 10.8 parts ·Charge transport material: CTM-1 ··· 7.2 parts Tetrahydrofuran 73.8 parts Toluene: 8.2 parts Tetrahydrofuran and toluene were mixed to prepare a mixed solvent. The polyarylate resin (1) and the charge transport material were added to the mixed solvent, and the mixture was stirred and mixed to obtain a coating liquid for forming a charge transport layer. The coating liquid for forming a charge transport layer was dip-coated onto the charge generation layer. The pull-up speed of the dip coating was controlled as shown in Table 1. The mixture was dried at a temperature of 150° C. for 40 minutes to form a charge transport layer having a layer thickness of 40 μm. Thus, a photoreceptor having an undercoat layer, a charge generating layer and a charge transport layer disposed on an aluminum substrate was obtained.
[0130] [ka]
[0131] <Examples 2 to 5 and Comparative Examples 1 to 5> A photoreceptor was manufactured in the same manner as in Example 1, except that in forming the charge generation layer, the charge generation material, the solvent, and the drying temperature were changed to the specifications shown in Table 1, and in forming the charge transport layer, the viscosity and solid content of the coating liquid and the pull-up speed in the dip coating were changed to the specifications shown in Table 1. In all of these Examples and Comparative Examples, the viscosity and solid content of the coating solution and the pull-up speed of the dip coating were controlled so as to obtain a charge transport layer having a thickness of 40 μm.
[0132] <Comparative Examples 6 to 9> A photoreceptor was manufactured in the same manner as in Example 1, except that in forming the charge generating layer, the drying temperature was changed to the specifications shown in Table 1, and in forming the charge transport layer, the type of binder resin, the addition of filler, the viscosity and solid content of the coating solution, and the pull-up speed in dip coating were changed to the specifications shown in Table 1. The following polycarbonate resin (1) was used as the binder resin for the charge transport layer. The charge transport layer contained 1.6 parts of polytetrafluoroethylene particles having an average particle size of 700 nm as a filler. In all of these comparative examples, the viscosity and solid content of the coating solution and the pull-up speed of the dip coating were controlled so as to obtain a charge transport layer having a thickness of 40 μm.
[0133] [ka]
[0134] <Photoreceptor performance evaluation> Each photoreceptor was mounted in an electrophotographic image forming apparatus DocuCentre-V C7775 (manufactured by FUJIFILM Business Innovation Co., Ltd.). In an environment with a temperature of 24°C and a relative humidity of 55%, 40,000 full-page cyan halftone images with a density of 30% were continuously printed on A3-sized plain paper.
[0135] [Uneven layer thickness] The thickness of the charge transport layer was measured before image formation. The measurements were taken at four locations at 90° intervals in the circumferential direction near one end of the photoreceptor in the axial direction, and at four locations at 90° intervals in the circumferential direction near the other end. An electromagnetic film thickness meter (Fisher Instruments, Permascope) was used for the measurements. The layer thicknesses at the four locations near one end were averaged, and the layer thicknesses at the four locations near the other end were averaged, and the difference between the average values was calculated. The results are shown in Table 2.
[0136] [Image density unevenness] The cyan full-surface halftone image on the 100th sheet was visually observed to check for stripes of uneven density caused by uneven thickness of the charge transport layer, and classified as follows. The results are shown in Table 2. A: There are no streaky unevenness in density. B: Faint streaks of uneven density are visible. C: Streaky uneven density is clearly observed.
[0137] [Wear rate] Before and after image formation, the thickness of the charge transport layer was measured at four locations at 90° intervals in the circumferential direction at the center of the axial direction of the photoreceptor. An electromagnetic film thickness meter (Fisher Instruments, Permascope) was used for the measurements. The layer thicknesses at the four locations were averaged, and the average value after image formation was subtracted from the average value before image formation to calculate the amount of wear. The wear rate (nm / kcy) was calculated by dividing the amount of wear by the number of photoreceptor running cycles. The results are shown in Table 2.
[0138] [Photoconductor life] The lower the wear rate (nm / kcy) of the charge transport layer, the longer the life of the photoconductor. The above wear rates (nm / kcy) were classified as follows. The results are shown in Table 2. A: Wear rate is less than 20nm / kcy B: Wear rate is 20nm / kcy or more, but less than 30nm / kcy C: Wear rate is 30nm / kcy or more
[0139] [Productivity] The faster the pull-up speed when dip-coating the charge transport layer, the faster the production line speed and the higher the productivity. The pull-up speeds when dip-coating the charge transport layer were classified as follows. The results are shown in Table 2. A: Pulling speed is 130 mm / min or more B: Pulling speed is less than 130 mm / min, 100 mm / min or more C: Pulling speed is less than 100 mm / min
[0140] In Comparative Example 6 and Comparative Example 8, the coating liquid for forming the charge transport layer contains a filler. Due to the time required for adding and dispersing the filler, it takes a long time to manufacture the photoreceptor in Comparative Example 6 and Comparative Example 8. Therefore, the productivity of Comparative Example 6 and Comparative Example 8 was evaluated as C.
[0141] [Table 1]
[0142] [Table 2]
[0143] The abbreviations listed in Table 1 represent the following compounds. HOGaPc: Hydroxygallium phthalocyanine ·ClGaPc: Chlorogallium phthalocyanine ·MIBK: Methyl isobutyl ketone ·PAR: Polyarylate PC: Polycarbonate ·PTFE: Polytetrafluoroethylene
[0144] The method for producing an electrophotographic photoreceptor according to the present disclosure includes the following aspects. (((1))) A method for producing an electrophotographic photoreceptor comprising: a conductive substrate; and a photosensitive layer having a charge generating layer and a charge transport layer disposed on the conductive substrate, the method comprising the steps of: forming the charge generating layer on the conductive substrate by coating; forming the charge transport layer on the surface of the charge generating layer by dip coating; the amount of solvent contained in the charge generating layer immediately before forming the charge transport layer is 0.1 ppm or more and 500 ppm or less; a distance Ra between an HSP of a solvent contained in the charge generating layer immediately before forming the charge transport layer and an HSP of a binder resin contained in a coating liquid for forming the charge transport layer is 8 or more and 10 or less; A method for manufacturing an electrophotographic photoreceptor. (((2))) The method for producing an electrophotographic photoreceptor according to (((1))), wherein the binder resin contains a polyarylate resin. (((3))) The method for producing an electrophotographic photoreceptor according to (((1))) or (((2))), wherein the charge transport layer has a thickness of 30 μm or more and 50 μm or less. (((4))) The method for producing an electrophotographic photoreceptor according to any one of (((1))) to (((3))), wherein a coating liquid for forming the charge transport layer has a viscosity of 500 mPa·S or more and 1000 mPa·S or less. (((5))) The method for producing an electrophotographic photoreceptor according to any one of (((1))) to (((4))), wherein in the dip coating for forming the charge transport layer, a pull-up speed is 100 mm / min or more and 200 mm / min or less.
[0145] According to (((1))), (((3))), (((4))) or (((5))), a production method is provided for producing an electrophotographic photoreceptor having excellent uniformity in the layer thickness of a photosensitive layer with good productivity, as compared with a case in which the amount of solvent contained in the charge generating layer immediately before forming the charge transport layer is less than 0.1 ppm or exceeds 500 ppm, or a case in which the distance Ra between the HSP of the solvent contained in the charge generating layer immediately before forming the charge transport layer and the HSP of the binder resin contained in the coating liquid for forming the charge transport layer is less than 8 or exceeds 10. According to (((2))), the photosensitive layer of the electrophotographic photoreceptor has superior abrasion resistance as compared with the case where the coating liquid for forming the charge transport layer does not contain a polyarylate resin. [Explanation of symbols]
[0146] 1 conductive substrate, 2 subbing layer, 3 charge generation layer, 4 charge transport layer, 5 photosensitive layer, 10A photoreceptor
Claims
1. A method for producing an electrophotographic photoreceptor comprising: a conductive substrate; and a photosensitive layer having a charge generating layer and a charge transport layer disposed on the conductive substrate, the method comprising the steps of: forming the charge generating layer on the conductive substrate by coating; forming the charge transport layer on the surface of the charge generating layer by dip coating; the amount of solvent contained in the charge generating layer immediately before forming the charge transport layer is 0.1 ppm or more and 500 ppm or less; a distance Ra between an HSP of a solvent contained in the charge generating layer immediately before forming the charge transport layer and an HSP of a binder resin contained in a coating liquid for forming the charge transport layer is 8 or more and 10 or less; A method for manufacturing an electrophotographic photoreceptor.
2. The method for producing an electrophotographic photoreceptor according to claim 1 , wherein the binder resin comprises a polyarylate resin.
3. The method for producing an electrophotographic photoreceptor according to claim 1, wherein the charge transport layer has a thickness of 30 μm or more and 50 μm or less.
4. 2. The method for producing an electrophotographic photoreceptor according to claim 1, wherein the viscosity of the coating liquid for forming the charge transport layer is from 500 mPa.s to 1000 mPa.s.
5. 2. The method for producing an electrophotographic photoreceptor according to claim 1, wherein a pull-up speed in the dip coating for forming the charge transport layer is 100 mm / min or more and 200 mm / min or less.
Citation Information
Patent Citations
Electrophotographic photoreceptor and method for manufacturing the same, and image forming apparatus having the same
JP2012242784A